The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2dt01007k
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-di-phosphonates as chelators for trivalent f-elements: kinetics, thermodynamic and interfacial study of Am(iii)/Eu(iii) solvent extraction

Abstract: The fractionation of high-level radioactive waste from nuclear power plants simplifies the handling of its components, and facilitates the reduction of radiotoxic effects on the environment. The search and study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In ref. 84, extraction kinetics and surface tension were also compared. The results indicated that while the surface properties of the extractant do influence the extraction rate, they are not the only determinant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ref. 84, extraction kinetics and surface tension were also compared. The results indicated that while the surface properties of the extractant do influence the extraction rate, they are not the only determinant.…”
Section: Resultsmentioning
confidence: 99%
“…This calculation scheme was successfully applied in the previous studies. 58 All optimized structures do not have imaginary frequencies. The Ahlrichs polarized basis set def2-TZVP 59 with triple z quality 60 was employed for all atoms.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Detailed information on the synthesis of pyridine-based ligands is presented in ref. 27. The synthesis of the phenanthroline ligand was carried out similarly 20 (see the ESI † for more information on spectral characterization of Phen-PO-C5).…”
Section: Synthesis Of Ligandsmentioning
confidence: 99%
“…18 In turn, neutral phosphorus-containing organic ligands are a promising class of substances for solvent extraction, including phenanthroline diphosphonates, [19][20][21] phenanthroline phosphine oxides [22][23][24][25] pyridine phosphine oxide, 26 and pyridine diphosphonates. 27,28 To date, the complexation properties of these compounds have primarily been investigated in relation to f-elements. Research exploring their complexation behavior with other types of elements, such as d-elements and maingroup elements, is limited.…”
Section: Introductionmentioning
confidence: 99%